The impact of Internet-enabled computer-aided design in the construction industry - Husin, Rizal; Mohamed Eshaq, Ahmad Rafi (Elsevier, 2003)
The advent of the Internet has opened up and given, particularly, the developing countries and the world in general, a transformation into collective intelligence [P. Levy, Becoming Virtual: Reality in the Digital Age, 1998, Plenum Publishing]1 societies linked to digital communication [A. Rafi M.E., Design creativity in emerging technologies, H. Von. Ars Electronica 2001: Takeover: Who's Doing the Art of Tomorrow, 2001. Springer Wein, New York]2. Apart from large corporations, the rapid evolution of borderless communication has also synergies between the art and science expertise to form low-cost internet-based networks that have become multi-million dollar companies within a short period of time (e.g. Linux) [A. Rafi M.E., Design creativity in emerging technologies, H. Von. Ars Electronica 2001: Takeover: Who's Doing the Art of Tomorrow, 2001. Springer Wein, New York]. In the context of architectural designs and construction industries, the birth of Internet-based computer-aided design (iCAD) solutions has offered a new dimension to architectural practice. The function of CAD has expanded as a tool to communicate and collaborate as well as to better control all phases of the architectural practices. This paper will review the current available iCAD tools and explore the possible utilisation of iCAD in architectural practices. The opportunities for modifying current professional practice standards to best use iCAD will be rationalised as well as the elements in ensuring the effectiveness of iCAD implementation. The final component of the paper will be an evaluation framework to measure the value of iCAD in an architectural practice. The framework will become an early platform for an architectural practice to decide and plan their future in utilising and applying iCAD in the most efficient way.